Early treatment of high risk chronic lymphocytic leukemia with alemtuzumab, rituximab and poly-(1-6)-beta-glucotriosyl-(1-3)- beta-glucopyranose beta-glucan is well tolerated and achieves high complete remission rates. Issue 8 (3rd August 2015) - Zent, Clive S.; Call, Timothy G.; Bowen, Deborah A.; Conte, Michael J.; LaPlant, Betsy R.; Witzig, Thomas E.; Ansell, Stephen M.; Weiner, George J.
Abstract : Poly-[1–6]-β-glucopyranosyl-[1–3]-β-glucopyranose (PGG) beta glucan is a Saccharomyces cerevisiae derived 1, 3/1, 6 glucose polymer with innate immune system activation potential. This phase I/II clinical trial enrolled 20 eligible patients with chronic lymphocytic leukemia with high-risk biological markers for early initial treatment with alemtuzumab, rituximab and PGG beta glucan (1–2–4 mg/kg/dose) over 31 days. PGG beta glucan at 4 mg/kg was well tolerated and used for the phase II study. There were three grade 3–4 toxicities at least possibly attributed to treatment. Nineteen (95%) patients responded to treatment with 13 (65%) complete responses. All patients were alive at a median follow-up of 24.4 months (range: 9.5–37). Eleven patients had progressive disease (median 17.6 months, 95% confidence interval [CI]: 9.7, 32.1) and eight patients were retreated (median 35.3 months, 95% CI: 17.9, not reached). We conclude that PGG beta glucan, alemtuzumab and rituximab treatment is tolerable and results in a high complete response rate.